Estratégias de relativização no português brasileiro e implicações para o ensino: o caso das cortadoras - Bispo, Edvaldo Balduino (2009)
This work consists of a cognitive-functional approach of relativization strategies of Brazilian Portuguese (BP), this is, standard relatives (with preposition or without it) and non-standard relatives (copiadora and the deletion pattern), and it emphasizes the last one. We investigate the use of the relative construction strategies in spoken and written texts produced by speakers from different school levels in a specific situation: a face-to-face interviewing. Our database is the corpora Discurso & Gramática: a língua falada e escrita na cidade do Natal e a língua falada e escrita na cidade do Rio de Janeiro. We contrast the use of the standard relative to the deletion pattern in prepositional context, by considering cognitive, social and interactional motivations for the use of the deletion pattern instead of the standard one. Our research leads us to verify that the deletion pattern is fixing as the preferred relativization strategy in prepositional contexts, and, in this way, it brings out a grammaticalization process in working. For this reason, we propose to take this relative construction as a common way to structure a relative clause, in the same way we take the standard pattern. Finally, we discuss the treatment of questions related to the processes of teaching and learning of Portuguese language and some suggestions are given in terms of class activities. We expect that the development of this research may give both support for the Portuguese teachers and suggestions to improve the teaching and learning process of Portuguese language, contributing in special to the treatment of the syntax of complex clauses.